Tuning the Reactivity of a Heterogeneous Catalyst using N‐Heterocyclic Carbene Ligands for C−H Activation Reactions - Palazzolo, Alberto; Naret, Timothée; Daniel‐Bertrand, Marion; Buisson, David‐Alexandre; Tricard, Simon; Lesot, Philippe; Coppel, Yannick; Chaudret, Bruno; Feuillastre, Sophie; Pieters, Grégory (Angewandte Chemie International Edition, 2020)
We report the dramatic impact of the addition of N‐heterocyclic carbenes (NHCs) on the reactivity and selectivity of heterogeneous Ru catalysts in the context of C−H activation reactions. Using a simple and robust method, we prepared a series of new air‐stable catalysts starting from commercially available Ru on carbon (Ru/C) and differently substituted NHCs. Associated with C−H deuteration processes, depending on Ru/C‐NHC ratios, the chemical outcome can be controlled to a large extent. Indeed, tuning the reactivity of the Ru catalyst with NHC enabled: 1) increased chemoselectivity and the regioselectivity for the deuteration of alcohols in organic media; 2) the synthesis of fragile pharmaceutically relevant deuterated heterocycles (azine, purine) that are otherwise completely reduced using unmodified commercial catalysts; 3) the discovery of a novel reactivity for such heterogeneous Ru catalysts, namely the selective C‐1 deuteration of aldehydes. The addition of N‐heterocyclic carbenes on Ru/C induces a catalytic activity switch to favor hydrogen isotope exchange over reductive deuteration. This catalyst modification led to an increase in regio‐ and chemoselectivity in the context of the C−H deuteration of pharmaceutically relevant substructures, as well as to the discovery of a novel reactivity for such heterogeneous Ru catalysts, namely selective C‐1 deuteration of aldehydes.